Perbandingan Kelimpahan dan Struktur Komunitas Zooplankton di Pulau Kodingareng dan Lanyukang, Kota Makassar - Hasanah, Alinda Nurbaeti; Rukminasari, Nita; Sitepu, Farida G (Hasanuddin University, 2014)
This study aimed to determine and compare community structure and assemblages species of zooplankton at Kodingareng and Lanyukang Island. This study used randomly sampling method and the sampling was conducted on July, August and October 2012. Data was analysed using at PRIMER software program. The results showed that zooplankton at Kodingareng and Lanyukang Isla nd had 48 taxa. 47 taxa was found when sampling at dry season and 25 taxa was found when the sampling at wet season. The species was only found at Kodingareng Island were Cypris and Amphipod, while the species was only found at Lanyukang Island was Luciferidae zoea, Tad Pole and Tintinid. The highest average of zooplankton abundance was found at dry season sampling at Lanyukang Island, account for 670 individu/L. The result of ANOSIM showed that the level of significance of zooplankton community structure a t Lanyukang and Kodingareng Island was 0.5%. Based on nMDS plot of zooplankton assemblages species between Lanyukang and Kodingareng Island showed clear seperation. The SIMPER result showed that there was no species seperator of community structure between those islands due to there was the same dominance of species, such as Calanoida, Cyclopoida, dan Chaetognatha.